2016
DOI: 10.1038/ni.3638
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional programs that control expression of the autoimmune regulator gene Aire

Abstract: Aire is a transcriptional regulator that induces promiscuous expression of thousands of genes encoding tissue-restricted antigens (TRAs) in medullary thymic epithelial cells (mTECs). While the target genes of Aire are well characterized, the transcriptional programs that regulate its own expression have remained elusive. Here we comprehensively analyzed both cis-acting and trans-acting regulatory mechanisms and found that the Aire locus was insulated by the global chromatin organizer CTCF and was hypermethylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 38 publications
3
49
0
Order By: Relevance
“…Moreover, the lysyl‐hydroxylase Jmjd6 (Jumonji domain‐containing protein 6) affects splicing of intron 2 of the Aire gene and is required for expression of mature Aire in mTECs, and Dgcr8 (DiGeorge syndrome critical region gene 8) is important for accumulation of Aire‐expressive mTECs in the thymus . Recent work from Herzig et al further demonstrated a very complex method of Aire expression regulation resulting from positive and negative mechanisms and the coordinated effort of multiple transcription factors, Irf4, Irf8, Tbx21, Tcf7, and Ctcfl. Whether patients with APECED‐like clinical disease with wildtype AIRE genotype have mutations in the aforementioned AIRE partners and regulators remains to be determined in future studies.…”
Section: Aire Partners and Regulationmentioning
confidence: 99%
“…Moreover, the lysyl‐hydroxylase Jmjd6 (Jumonji domain‐containing protein 6) affects splicing of intron 2 of the Aire gene and is required for expression of mature Aire in mTECs, and Dgcr8 (DiGeorge syndrome critical region gene 8) is important for accumulation of Aire‐expressive mTECs in the thymus . Recent work from Herzig et al further demonstrated a very complex method of Aire expression regulation resulting from positive and negative mechanisms and the coordinated effort of multiple transcription factors, Irf4, Irf8, Tbx21, Tcf7, and Ctcfl. Whether patients with APECED‐like clinical disease with wildtype AIRE genotype have mutations in the aforementioned AIRE partners and regulators remains to be determined in future studies.…”
Section: Aire Partners and Regulationmentioning
confidence: 99%
“…Additionally, there are proteins that, despite not interacting with AIRE, participate in the transcriptional complex associated with the expression of PTAs in mTECs . Many of these molecules even regulate Aire itself …”
Section: Controlling the Expression Of Peripheral Tissue Antigensmentioning
confidence: 99%
“…10 Many of these molecules even regulate Aire itself. 47 Recently, the group of Benoist/Mathis at Harvard University in Boston, MA, have found that some AIRE partners, especially those associated with the DNAdamage response, localize preferentially on chromatin sections known as super-enhancers, as for example TOPO 1. 48 In summary, Aire leads to the activation of PGE in mTECs when it is recruited into the transcriptional start sites (TSS) of most genes.…”
Section: Controlling the Expression Of Peripheral Tissue Antigensmentioning
confidence: 99%
“…24,26,29 Granulocyte macrophage colony-stimulating factor–driven moDC differentiation requires expression of functional IRF4 and CEBPB. 56,62,67,74 CEBPB can promote moDC differentiation by counteracting IRF8 effects. 67 Notably, KLF4 induces a set of monocyte lineage–associated molecules and is a key switch factor regulating differentiation of monocytes into moDCs.…”
Section: Transcription Factors and Generation Of Distinct DC Subsetsmentioning
confidence: 99%